Young Adult Literature in the English Language Arts Classroom: A Survey of Middle and Secondary Teachers' Beliefs about YAL - Ann Smith; Lisa Hazlett; Sean Lennon (University of Oklahoma Libraries, 2018)
The goal of this survey study was to discover the reasons for the use or nonuse of young adult literature in the classroom.  This study revealed that YAL has gained in popularity with middle school teachers. New information, presented from qualitative data analysis on open-ended survey responses, adds to previous research on how teachers use YAL in secondary classrooms.